Historical reconstruccion of the San Miguel de Cerro Gordo Prison in the Camino Real de Tierra Adentro in México - Acosta, Roberto Carrillo (2021)
In the historiography of the fortifications, it is worrisome that there is little material produced, but that which has been generated in northern Mexico is even scarcer. It is also worrying that material heritage is being lost, there is more and more neglect and ruin in material evidence, including, in many cases, total loss. A great area of opportunity opens up here before the historical, but also virtual reconstruction of forgotten heritage spaces, and their subsequent enhancement, is the case of the Presidio of San Miguel de Cerro Gordo.